Pembuatan Bibliografi Beranotasi Koleksi Audio Visual Dinas Perpustakaan dan Kearsipan Kota Padang Panjang - Wulan Afni Sundari; Desriyeni Desriyeni (Ilmu Informasi Perpustakaan dan Kearsipan, 2017)
The writing of this paper discusses about the condition of audio visual collections in the library and Archives Department of the city of Padang Panjang and annotated bibliography creation of audio visual collections in the library and Archives Department of the city of Padang Panjang. This paper aims to describe the condition of audio visual collections in the library and Archives Department of the city of Padang Panjang and annotated bibliography creation of audio visual collections in the library and Archives Department of the city of Padang Panjang to better facilitate in rediscovering the needed information at any time. Data analysis using descriptive method used. Data collected through direct observation or research in the service of the library and Archives of the city of Padang Panjang. From the data analysis through observation and direct research, collected as many as 65 films. Based on penganalisisan data, it can be concluded that the stages in the manufacture of audio visual collection of annotated bibliography as follows: (a) the determination of the title bibliography; (b) the collection of library materials or information retrieva; (c) the selection of references; (e) the making of a keyword; (f) the preparation of an annotated bibliography on the index, audio visual collection contains index author index; (g) a typing manuscripts bibliography; (h) the inspection of the final manuscript.Keywords: bibliografi, audio visual